Importance of Pragmatics in The Usage of A Language for Communication - Sattorova Feruza Elmurodovna (Web of Journals Publishing, 2023)
This article is an anchor for the understanding the importance of pragmatics in the forming process of communicative competence. The concept of pragmatics may possibly require some further explanation, although it has been researching by scholar and linguists for over 4 decades. Therefore, implementing teaching pragmatics has now been developing and ongoing process in language teaching pedagogy.
Keywords: CEFR, native-like proficiency, discourse competence, functional competence, design competence, Linguistic competences, Grice’s “co-operative principle”.